PENDAMPINGAN PEMBUATAN DEMPLOT SAYURAN KELOMPOK PKK DESA DARU KECAMATAN KAO UTARA - Dadalaka, Iranto; Ada, Ricky R.; Patty, Zeth; Kastanja, Ariance Y.; Kour, Femsy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
This community service activity aims to increase the knowledge and skills of PKK members in cultivating vegetable plants independently. Activities were carried out in Daru Village targeting the PKK group, using counseling methods and creating PKK garden demonstration plots. The results of the service activities show that the activities carried out have increased the knowledge and skills of PKK group members which include the ability to recognize vegetable seeds based on their shape and color, differentiate between how to plant seeds, plant spacing for each type of vegetable, explain when to fertilize, differentiate the harvest age for each type of vegetable, explains the harvest time for the vegetable crops planted, which in the future can encourage an increase in the quality of family food